Shunt active power filter based on particle swarm optimization-wavelet transform and zero crossing controller - Thajeel, Ekhlas Mhawi (2018)
One of the serious problems with modern electrical loads is harmonics, which is generated from nonlinear loads. Harmonics can lead to excessive heat and noise in the loads and create large amount of energy losses either in transmission systems or distribution systems. Compensation of these harmonics substantially improves the power factor and reduces the total harmonic distortion index (THD). This means that the system can transfer more active power without having to increase the capacity. Traditionally, passive filters have been used to remove harmonics but for their intrinsic downsides, they have been replaced by active power filter (APF). APF has superior filtering characteristics and dynamic response compared to passive filters. Over the past decades, there has been a significant increase in interest of APFs and its control methods. There are three factors that drives the research in this thesis; (1) although many studies has proven that zero crossing information is crucial in many control signal, there have been no attempt on incorporating zero crossing controller (ZCC) in APF DC link voltage regulation, (2) Particle swarm optimization (PSO) has been adapted for DC link voltage regulation in APF, but there is lack of evidences of dynamic performance investigation for such techniques, and (3) Synchronous Reference Frame (SRF) has been widely adopted for harmonics extraction in APF, although it has been found out to have a slow response. Discrete Wavelet Transform (DWT) on the other hand, is a good candidate for harmonics extraction, but have not received enough attention in the literature due to its relatively high complexity. This study attempts to tackle these gaps by introducing ZCC, PSO and DWT as a new fusion of controller for APF. The new controller is thoroughly developed and rigorously simulated in MATLAB-Simulink environment. The harmonics source is a 5.5 kW nonlinear load mimicking a real-life load from previous practical studies. The test cases ranges from steady state, various loads, dynamic loads and unbalance voltage. The results show that DWT outperforms SRF in all test cases with average 53% improvement. It is also found out that the combination of PSO and DWT yield better results in general. It is a superior controller as compared to traditional Zeigler-Nichols tuned Proportional Integral (PIZN) controller and Fuzzy Logic Controller (FLC). However, ZCC-DWT consistently yields better performance than all other controller in one of the test case; the unbalance voltage. As conclusion, DWT is a better candidate for harmonics extraction in APF, as compared with SRF. Together with DWT, PSO and ZCC perform very well in different test cases. This new combination of controller is a good candidate to be widely accepted as a new controller in modern APF.